Pengaruh penggunaan teknologi akuntansi terhadap efisiensi pengelolaan keuangan UMKM di Kota Malang - Sulistiyowati, Yayuk; As’adi, As’adi (e-Journal Perdagangan Industri dan Moneter, 2023)
Technological progress is driving economic change in all industries. Micro, small and medium enterprises are facilitated to manage their finances efficiently by providing accurate information for stakeholders, both stakeholders and business owners. Knowledge of technology that is still relatively low has an impact on the low ability of micro, small and medium enterprises in utilizing technology. The research objective was to examine the effect of using accounting technology on the efficiency of financial management of micro, small and medium enterprises in Malang City. The data used in this study is quantitative data, while the data source used is primary data with data collection techniques using questionnaires. Simple regression analysis method used in this study. The population in this study is Micro, Small and Medium Enterprises in Malang City. The results of the research show that there is an effect of accounting technology on the efficiency of financial management of micro, small and medium enterprises.